Question
upstudy study bank question image url

\( \frac{x^{2}+5 x}{2}+\frac{12}{x^{2}+5 x}=-5 \) let \( x^{2}+5 x=a \)

Ask by Mathis King. in South Africa
Feb 03,2025

Real Tutor Solution

Tutor-Verified Answer

Answer

The solutions are \( x=-4, -3, -2, -1 \).

Solution

Solve the equation \( \frac{x^{2}+5x}{2}+\frac{12}{x^{2}+5x}=-5 \). Solve the equation by following steps: - step0: Solve for \(x\): \(\frac{x^{2}+5x}{2}+\frac{12}{x^{2}+5x}=-5\) - step1: Find the domain: \(\frac{x^{2}+5x}{2}+\frac{12}{x^{2}+5x}=-5,x \in \left(-\infty,-5\right)\cup \left(-5,0\right)\cup \left(0,+\infty\right)\) - step2: Multiply both sides of the equation by LCD: \(\left(\frac{x^{2}+5x}{2}+\frac{12}{x^{2}+5x}\right)\times 2\left(x^{2}+5x\right)=-5\times 2\left(x^{2}+5x\right)\) - step3: Simplify the equation: \(x^{4}+10x^{3}+25x^{2}+24=-10x^{2}-50x\) - step4: Move the expression to the left side: \(x^{4}+10x^{3}+25x^{2}+24-\left(-10x^{2}-50x\right)=0\) - step5: Calculate: \(x^{4}+10x^{3}+35x^{2}+24+50x=0\) - step6: Factor the expression: \(\left(x+1\right)\left(x+2\right)\left(x+3\right)\left(x+4\right)=0\) - step7: Separate into possible cases: \(\begin{align}&x+1=0\\&x+2=0\\&x+3=0\\&x+4=0\end{align}\) - step8: Solve the equation: \(\begin{align}&x=-1\\&x=-2\\&x=-3\\&x=-4\end{align}\) - step9: Check if the solution is in the defined range: \(\begin{align}&x=-1\\&x=-2\\&x=-3\\&x=-4\end{align},x \in \left(-\infty,-5\right)\cup \left(-5,0\right)\cup \left(0,+\infty\right)\) - step10: Find the intersection: \(\begin{align}&x=-1\\&x=-2\\&x=-3\\&x=-4\end{align}\) - step11: Rewrite: \(x_{1}=-4,x_{2}=-3,x_{3}=-2,x_{4}=-1\) The solutions to the equation \( \frac{x^{2}+5x}{2}+\frac{12}{x^{2}+5x}=-5 \) are \( x=-4, -3, -2, -1 \).

Reviewed and approved by the UpStudy tutoring team

error msg
Explain
Simplify this solution

Beyond the Answer

To simplify things, let's substitute \( a = x^{2} + 5x \). The equation then becomes \( \frac{a}{2} + \frac{12}{a} = -5 \). Multiplying the entire equation by \( 2a \) (to eliminate the fractions) yields \( a^2 + 24 = -10a \). Rearranging gives us a quadratic equation: \( a^2 + 10a + 24 = 0 \). Now you can use the quadratic formula \( a = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \) to find values for \( a \). Next, once you've found the values for \( a \), substitute back to \( x^{2} + 5x \) in order to find the corresponding \( x \) values. Don’t forget to check for possible extraneous solutions resulting from our manipulations!

Related Questions

Latest Algebra Questions

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy